Transcriptomic responses of Serratia liquefaciens cells grown under simulated Martian conditions of low temperature, low pressure, and CO2-enriched anoxic atmosphere. Issue 1 (December 2018) - Fajardo-Cavazos, Patricia; Morrison, Michael; Miller, Kathleen; Schuerger, Andrew; Nicholson, Wayne
Abstract Results from previous experiments indicated that the Gram-negative α-proteobacteriumSerratia liquefaciens strain ATCC 27592 was capable of growth under low temperature (0 °C), low pressure (0.7 kPa), and anoxic, CO2 -dominated atmosphere–conditions intended to simulate the near-subsurface environment of Mars. To probe the response of its transcriptome to this extreme environment, S. liquefaciens ATCC 27592 was cultivated under 4 different environmental simulations: 0 °C, 0.7 kPa, CO2 atmosphere (Condition A); 0 °C, 101.3 kPa, CO2 atmosphere (Condition B); 0 °C, 101.3 kPa, ambient N2 /O2 atmosphere (Condition C); and 30 °C, 101.3 kPa, N2 /O2 atmosphere (Condition D; ambient laboratory conditions). RNA-seq was performed on ribosomal RNA-depleted total RNA isolated from triplicate cultures grown under Conditions A-D and the datasets generated were subjected to transcriptome analyses. The data from Conditions A, B, or C were compared to laboratory Condition D. Significantly differentially expressed transcripts were identified belonging to a number of KEGG pathway categories. Up-regulated genes under all Conditions A, B, and C included those encoding transporters (ABC and PTS transporters); genes involved in translation (ribosomes and their biogenesis, biosynthesis of both tRNAs and aminoacyl-tRNAs); DNA repair and recombination; and non-coding RNAs. Genes down-regulated under all Conditions A, B, and C included: transporters (mostly ABC transporters); flagellar and motility proteins; genes involved in phenylalanine metabolism; transcription factors; and two-component systems. The results are discussed in the context of Mars astrobiology and planetary protection.